Strategic Management in Improving the Quality of Health Services at the Tuntungan Health Center - Wasiyem, Wasiyem; Wuni Barokah; Aprida Khairani Ritonga; Nur Cahaya Hasibuan; Fika Ayu Cahaya Hsb; Mewani Sinaga; Mutiara Salsabila; Ika Amanda; Maulidia Khairiah (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze strategic management in improving the quality of health services at the Tuntungan Health Center. The method used was in-depth interviews with health workers and health center managers, as well as direct observation of the service process. The results of the study show that the commitment of health workers in providing the best service is a key factor in building patient trust. The implementation of timely and standard service procedures creates a supportive environment for patients. Responsiveness to patient complaints is also an advantage of the Health Center, where a good communication system allows staff to respond to complaints quickly, thereby increasing patient satisfaction. Quality assurance and service safety are sought through the implementation of strict standard operating procedures (SOPs), providing a sense of security for patients. In addition, the empathetic attitude shown by healthcare workers contributes to the positive experience of patients, making them feel valued and cared for. However, the study also found challenges related to the condition of physical facilities and infrastructure that still need development, which can affect patient comfort. Routine training efforts for health workers and collaboration with hospitals and other health facilities are strategic steps to expand access to services and improve service quality. The conclusion of this study emphasizes the importance of continuous improvement in these aspects to achieve optimal health services and meet community expectations.